A study in Development of Control Chart Pattern Recognition Scheme Based on Literature - Baharuddin, Muhammad Afiq; Masood, Ibrahim (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Control chart pattern recognition (CCPR) is an important aspect in statistical process control (SPC). The abnormal patterns occurred in control charts can be related to specific assignable causes that have a negative impact on process stability. The recognizing of control chart pattern has provided a various developed approach over the years. In point of fact, numerous research studies literature with various development criteria and different approach trends have been published. Despite the abundance of research studies literature on the CCPR areas, there has been a difficulty to examine and analyze the development criteria and approach trends of CCPR schemes studies. Therefore, this study proposes a classification development criteria scheme for analyzed and classified the development criteria and trends in CCPR schemes research studies article. About 21 published research studies articles of CCPR schemes within 2011 – 2021 were analyzed and classified. The following are some of the study major findings. Firstly, most of the CCPR research studies still worked with the common development criteria and trends from previous decade. Secondly, some identification on implemented input representation and learning algorithm of researcher developed method. Moreover, the percentage of research studies for methods detecting the control chart pattern (CCPs) using support vector machine (SVM) is increasing. Next, there are some modifications on development of pattern recognizer model with an added feature. Furthermore, majority of the research studies performance criteria are using recognition accuracy, data mining based, and correct recognition ratio for performance measure. Generally, the common development criteria and trends are still widely used in the research of CCPR schemes and the other development criteria are expected to be implemented more in the future due to its promising contribution. Hence, this study will provide a summarized information that is useful for further development of CCPR schemes